Sea Level Variation in the Sea of Japan - Lisitzin, Eugenie (The International Hydrographic Review, 2015)
The problem of the seasonal variation in sea level in oceans and seas can at the present time be solved only approximately. Although practically all recent research indicates that variation in atmospheric pressure and changes in water density — and correspondingly in water volumbibe — greatly contribute to sea level fluctuations and that these two factors are of decisive signficance for the seasonal cycle in sea level, there remain a considerable number of questions which are so far unsolved. This is especially so in the type of sea where the water balance is marked enough to be an important factor, or where the piling-up effect of wind is very pronounced, showing in addition seasonal changes. The contribution of these supplementary factors should therefore not be underestimated. It must also be remembered in this connection that the results can never be generalized. Every sea must be studied separately and special attention has to be paid to the features characterizing each particular basin. Moreover the problem of mean sea level in the world ocean requires additional study. In spite of the fact that significant preliminary work has already been done, a more or less final result can be reached only by means of the numerical evaluation of a large number of observed data on water temperature and salinity, of intensified hydrographic work at sea, and continuous water level recording along the coasts and on oceanic islands on an expanded scale.